A novel cryogenic condensation system based on heat-driven refrigerator without power input for volatile organic compounds recovery. (15th June 2021) - Hao, Xu; Xiafan, Xu; Liubiao, Chen; Jia, Guo; Junjie, Wang
Highlights: A zero-emission VOCs condensation system without external power supply is proposed. Burning 9% of the VOCs achieves the purification treatment of the remaining 91%. The recovery rate of burning inlet gas is higher than that of burning liquefied VOCs. Recovering the cold of the purified gas improves the VOCs recovery rate by 5.5%. Abstract: Volatile organic compounds (VOCs) are important precursors of pollutants such as PM2.5 and ozone, and the development of their treatment technologies is of great significance to environmental protection and economic development. The current VOCs destruction technology, such as the combustion method, has low operating costs, but there is a large waste in the treatment of high-value gas; while the current VOCs recovery technology, such as the condensation method based on refrigerator cooling, can recover high-value gas, but it still has some unsatisfactory aspects in terms of emission concentration, refrigerant use, and power supply. In this paper, a novel cryogenic condensation system based on a heat-driven refrigerator without power input for oil gas VOCs recovery was proposed. The heat obtained by burning part of the oil gas VOCs is employed to drive a thermoacoustic refrigerator using helium as working gas to realize the recovery of the remaining oil gas VOCs, which has the advantages of not relying on external power supply, using natural working fluid, and zero-emission of oil gas. A thermodynamic calculation model was established to quantitatively calculate the recovery efficiency. The results show that the remaining 91.0% of the oil gas VOCs can be recovered by burning 9.0% of the oil gas VOCs when the refrigeration temperature is 200 K, the heat source temperature is 873 K and the concentration is 33.5% at 100 kPa. And compared with the method of burning part of the liquefied VOCs, the method of burning part of inlet gaseous VOCs to drive the refrigerator has a higher recovery efficiency (around 10%). The effects of the refrigeration temperature, the heat source temperature, VOCs concentration, VOCs inlet pressure, and refrigerator efficiency on the system were also analyzed.